What Erasmus students expected and experienced during the course of People in Organisations at a Business and Administration School.: Teaching HRM in multicultural contexts. - Marques, Maria Amélia (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
Today Erasmus is not only the most widespread student mobility programme in the EU, but it has also become mandatory in some of the business degrees. It also appears to be one of the best “prerequisites” for students to enhance their employability and/or succeed in their future careers. Notwithstanding the importance of employability, this appears to be one of several different reasons which motivates students to participate in the programme. Others being: the opportunity to study in high quality academic environments; the opportunity to carry out extracurricular activities during this period, and/or for vocational reasons; to improve their linguistic skills (particularly English); to have the opportunity to meet people from other cultures; to become more independent, etc. (Pietro and Page, 2008; Vaicekauskas.; Duoba and Kumpikaitté-Valiuniene, 2013; Marques and Almeida, 2014a). As a teacher of the courses in the field of Organisational Behavior and Human Resource Management of an International Module designed for incoming Erasmus students, and have carried out two previous exploratory studies about motivations and expectations of Erasmus students in the two courses (Marques and Almeida, 2014a; Marques and Almeida, 2014b), in this presentation the aim was to analyse students’ expectations and competences developed during the course of People in Organisations. The course was solely taught in English during the Autumn-Winter semester. Active pedagogic methods were used, and, in every class, students worked in multicultural groups to solve problems about people in organisations which were addressed in a meso approach. Thus, always focusing on national, cultural as well as organizational and individual factors that shape organizational behavior. Students were asked to do oral presentations, pitches and role playing. The assessment system consisted of participation in class, an oral presentation in group and a written test. The latter included questions about their experience and competences developed in the course and during their stay. This study is a follow-up of the work previously carried out and abovementioned. Methodologically it consisted of a qualitative study carried out in two stages: at the beginning of the semester a questionnaire was passed out to the 36 students enrolled in the course about their expectations and motivations for Erasmus and for the course. At the end of the semester students answered questions about the competences they perceived they developed and their experience. Students were from the Bachelor and Master’s degrees. Their average age was 21 years old and all of them were from western and eastern European higher education institutions. Our main findings were that Erasmus students’ motivations for the course, and Erasmus, were the opportunity to develop culture awareness competences and enhance competences of working in multicultural groups, followed by the motivation to improve their English, the knowledge of the Portuguese language and for vacation reasons. Personal development and independence were the least considered. As to the competences they perceived they developed, culture awareness and the ability to work in multicultural groups is the most salient but it was followed by independence, autonomy, initiative and personal development, which was considered before the improvement of English skills. The perception of competences to work in international assignments is also mentioned but it is not very salient. Marques, M.A. & Almeida, A.J. (2014a). Promoting training and skill development for international employability: the motivations of Erasmus’ students in the field of management, in Gomes, J. & Coelho, J.P., Values in shock: the role of contrasting management, economic, and religious paradigms in the workplace, (pp. 107-114). ISSWOV - International Society for the Study of Work & Organizational Values, USA. Marques, M.A. e Almeida, A. J. (2014b). Erasmus students’ expectations and competences development: an exploratory study of incoming students in Portugal.in SGEM, Education and Education Research,SGEM. Bulgaria: STEF92 Technology Ltd.:287-294 .ISBN:978-619-7105-24-7; ISSN:2367-5659, DOI:10.5593/sgemsocial12014B13 Pietro G. & Page, L. (2008). Who Studies Abroad? Evidence from France and Italy. European Journal of Education, UK, vol. 43/issue, No. 3, pp. 389-398, Vaicekauskas, T.; Duoba, K. & Kumpikaitté-Valiuniene, V. (2013) The role of international mobility in students’ core competences development. Economics and Management, Lithuania, vol. 18,/issue 4, pp. 847-856.